The first record of Iris setosa (Iridaceae) in Europe - Boltenkov, Eugeny V.; Menshakova, Marija Y.; Gainanova, Ramziya I.; Rumjantseva, Zinaida Y. (Phytotaxa, 2020)
Iris setosa is one of the widespread Iris species in Northeast Asia and North America. In 2018, it was found for the first time in Europe, on Kildin Island (Murmansk Oblast, Russian Federation). The presence of this plant on the island and its disjunct range are discussed. To facilitate further detection and identification, a general morphological description, information about the original material of the name I. setosa, and supporting illustrations are here provided.